Prevalence of cardiometabolic risk factors and selected cardiovascular diseases in hypertensive and normotensive participants in the adult Polish population: The WOBASZ II study. Issue 28 (10th July 2020) - Niklas, Arkadiusz; Marcinkowska, Justyna; Kozela, Magdalena; Pająk, Andrzej; Zdrojewski, Tomasz; Drygas, Wojciech; Piwońska, Aleksandra; Bielecki, Wojciech; Kozakiewicz, Krystyna; Tykarski, Andrzej
Abstract : Abstract: Hypertension is one of the most important causes of cardiovascular disease (CVD) incidence and mortality. The aim of the study was to assess the prevalence of metabolic syndrome and its individual components i.e., diabetes, obesity, elevated triglycerides (TG), low HDL (high-density lipoprotein) cholesterol, as well as selected manifestations of CVD i.e., atrial fibrillation (AF), peripheral artery disease (PAD), coronary artery disease (CAD), myocardial infarction (MI), and stroke in persons with and without hypertension in the Polish population. The analysis included participants of Polish multicentre WOBASZ II Study i.e., 6163 persons aged 19 and above. The Mantel Haenszel anlysis and multidimensional logistic regression model were used to assess the relations between the prevalence of metabolic syndrome and its individual components as well as selected manifestations of CVD with hypertension. Compared to normotensives, metabolic syndrome was over 5 times more prevalent in participants with hypertension (OR = 5.35, 95% CI:4.71–6.09). Components of the metabolic syndrome and selected manifestations of CVD were more prevalent in participants with hypertension compared to normotensives. The Mantel-Haenszel odds ratios (95% confidence intervals) were as follows: obesity counted as BMI > 30 kg/m 2 OR = 2.58 (2.26–2.96), raised triglycerides OR = 2.34 (2.07–2.64), reduced HDL-C OR = 1.81 (1.59–2.06), metabolic syndrome OR = 5.35 (4.71–6.09), diabetes OR = 2.54 (1.98–3.26), AF OR = 1.47 (1.09–2.00), PAD OR = 1.51 (1.14–1.99), CAD OR = 1.94 (1.52–2.49), MI OR = 1.89 (1.32–2.70), hospitalization due to HF OR = 2.02 (1.43–2.87), hospitalization due to exacerbation of CAD OR = 2.13 (1.58–2.86), hospitalization due to revascularization OR = 2.38 (1.49–3.80), hospitalization due to stroke OR = 1.72 (1.1–2.68). Compared to normotensive participants, persons with hypertension had higher prevalence of diabetes, obesity, MS, PAD, CAD, stroke, MI and AF, and more frequent need for hospitalization due to HF, exacerbation of CAD and for coronary revascularization.